ANALISIS TEORI RESEPSI TENTANG REPRESENTASI PERPUSTAKAAN PERGURUAN TINGGI PADA VIDEO PERESMIAN GEDUNG PUSAT INFORMASI DAN PERPUSTAKAAN UNIVERSITAS NEGERI PADANG - Ikhsan, Risky Jumatul; Prihatin, Silverius Djuni (Program Studi Perpustakaan dan Ilmu Informasi, Fakultas Bahasa dan Seni, Universitas Negeri Padang, 2024)
The development of technology and digitalization has encouraged various institutions, including university libraries, to utilize digital platforms such as YouTube as promotional tools. This study analyzes the representation of the Universitas Negeri Padang (UNP) library in the promotional video titled